2021
DOI: 10.3389/fncel.2021.680126
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelets in the Stimulation of Neuronal Synaptic Plasticity, Electric Activity, and Oxidative Phosphorylation: Possibilities for New Therapy of Neurodegenerative Diseases

Abstract: The central nervous system (CNS) is highly vascularized where neuronal cells are located in proximity to endothelial cells, astroglial limitans, and neuronal processes constituting integrated neurovascular units. In contrast to many other organs, the CNS has a blood-brain barrier (BBB), which becomes compromised due to infection, neuroinflammation, neurodegeneration, traumatic brain injury, and other reasons. BBB disruption is presumably involved in neuronal injury during epilepsy and psychiatric disorders. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 88 publications
2
14
0
Order By: Relevance
“… 71 Moreover, direct contact with brain glycolipid structures present in the membranes of astrocytes further activates platelets and stimulates neuroinflammation, 53 leading to immune cell recruitment into the brain parenchyma 74 and the simultaneous release of trophic factors. 27,53,72 Interestingly, this cascade of events creates a microenvironment where proinflammatory cytokines, neurotrophic factors, and neurotransmitters coexist, which, in response to CNS damage, can stimulate new synapse formation and axonal regrowth. 27 A specific role in the modulation of neuroinflammation has been assigned to the α-granule chemoattractants CXCL4 and CCL5 through monocyte recruitment, or MIP-1a (macrophage inflammatory protein-1a) 67,75 because of interaction with immune cells, BBB cellular components, astrocytes and microglia, as well as neurons themselves.…”
Section: Platelets and Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“… 71 Moreover, direct contact with brain glycolipid structures present in the membranes of astrocytes further activates platelets and stimulates neuroinflammation, 53 leading to immune cell recruitment into the brain parenchyma 74 and the simultaneous release of trophic factors. 27,53,72 Interestingly, this cascade of events creates a microenvironment where proinflammatory cytokines, neurotrophic factors, and neurotransmitters coexist, which, in response to CNS damage, can stimulate new synapse formation and axonal regrowth. 27 A specific role in the modulation of neuroinflammation has been assigned to the α-granule chemoattractants CXCL4 and CCL5 through monocyte recruitment, or MIP-1a (macrophage inflammatory protein-1a) 67,75 because of interaction with immune cells, BBB cellular components, astrocytes and microglia, as well as neurons themselves.…”
Section: Platelets and Neuroinflammationmentioning
confidence: 99%
“… 27,53,72 Interestingly, this cascade of events creates a microenvironment where proinflammatory cytokines, neurotrophic factors, and neurotransmitters coexist, which, in response to CNS damage, can stimulate new synapse formation and axonal regrowth. 27 A specific role in the modulation of neuroinflammation has been assigned to the α-granule chemoattractants CXCL4 and CCL5 through monocyte recruitment, or MIP-1a (macrophage inflammatory protein-1a) 67,75 because of interaction with immune cells, BBB cellular components, astrocytes and microglia, as well as neurons themselves. Together, these observations highlight the contribution of various platelet factors in neuroinflammation and have provided incentives for preclinical studies where the protective effect of antiplatelet adjunct therapy, such as aspirin, has been examined.…”
Section: Platelets and Neuroinflammationmentioning
confidence: 99%
“…Latest experiments found that platelets can enter the CNS parenchyma and directly interact with neuronal cells [127]. When platelets are activated in the CNS, they release various pro-inflammatory mediators, neurotrophic factors, and neurotransmitters, which stimulate neuronal electrical and synaptic activity and promote the development of new synapses and axonal reconstruction near the site of damage [127].…”
Section: Temporarily and Reversibly Increases Of The Bbb Permeability...mentioning
confidence: 99%
“…Latest experiments found that platelets can enter the CNS parenchyma and directly interact with neuronal cells [127]. When platelets are activated in the CNS, they release various pro-inflammatory mediators, neurotrophic factors, and neurotransmitters, which stimulate neuronal electrical and synaptic activity and promote the development of new synapses and axonal reconstruction near the site of damage [127]. Kopeikina and Ponomarev emphasize [127]: "Platelets and their secreted factors could affect many cell types involved in the regulation of BBB integrity including endothelial cells, astroglia, and pericytes".…”
Section: Temporarily and Reversibly Increases Of The Bbb Permeability...mentioning
confidence: 99%
See 1 more Smart Citation